Desarrollo del manual de buenas prácticas de manufactura (BPM) para la microempresa Choco Warmi del cantón Echeandía comunidad San Gerardo, Bolívar - Freire Chamorro, Marjorie Mireya (2024)
The main objective of this research project was to develop a manual of good manufacturing practices for the cocoa processing plant of the San Gerardo producer’s association. The BMP guarantee the safety of the production processes and therefore of the final product, they have several operating principles, among them: structure and hygiene of the facilities, personnel, raw materials, control of the production processes, production hygiene, storage, transportation of raw materials and end of the product. At the moment the production part is artisanal, and since it is handled in an artisanal manner, technological tools that can guarantee the safety of the products as well as the optimization of the production processes have not been considered. A bibliographic research was carried out in order to know the current national regulations to obtain healthy products, such as the INEN regulations for cocoa beans at the same time for the production of chocolate, the ARCSA-2023-003-AKRG regulations that describe what that must be met in facilities, equipment and utensils, personnel obligations, raw materials and supplies, production operations, packaging, labeling, storage, quality control, which are fundamental for the development of the manual. Field visits were carried out inside the chocolate factory, to find out whether or not the different parameters were met according to the National Agency for Health Regulation, Control and Surveillance, which the food processing company must comply with.